A new species of Pseudopaludicola (Anura, Leptodactylidae) from northern Brazil - Giaretta, Ariovaldo A.; de C. Kokubum, Marcelo N. (Zootaxa, 2003)
We describe a new species, Pseudopaludicola canga, from the Serra dos Carajás highlands in Brazilian Amazonian forest. The new species is a member of the Pseudopaludicola pusilla group and is characterized mainly by its large size. The described species may represent another endemic species of the Serra dos Carajás.